Factors Predicting Depression, Anxiety, and Stress of Undergraduate Students in the Eastern Region of Thailand - Srisopa, Pornpan; Moungkum, Saifone; Hengudomsub, Pornpat (Nursing Science Journal of Thailand, 2023)
Purpose: This study aimed to exploring prevalence and predictive factors of depression, anxiety, and stress among undergraduate students in a university, in the eastern region of Thailand. Design: Correlational predictive design. Methods: The study samples consisted of 400 undergraduate students from a university in the eastern region were recruited. Groups of disciplines and affiliated faculties were stratified; and six faculties were randomly selected. Eligible students were recruited using convenience sampling. Data were collected by using three self-report questionnaires including socio-demographic data, Depression Anxiety and Stress Scale (DASS-21), and Difficulties in Emotion Regulation Scale – short form (DERS-SF). The collected data were analyzed by binary logistic regression. Main findings: The results showed that the prevalence rates of depression, anxiety, and stress were in a range of variation from severe to extremely severe levels, percentage of 20.7%, 32.2%, and 15.4% respectively. A factor associated with depression was the difficulties in emotion regulation (p < .001). Factors predicting anxiety were the difficulties in emotion regulation (p < .001) and a history of physical illness (p < .05). Factors predicting stress were the difficulties in emotion regulation (p < .001), a history of mental illness (p < .05), and experienced stressful events (p < .001). Conclusions and recommendations: The result suggests that more than 15 percent of the students had experienced severe negative emotions including depression, anxiety, and stress. The factor that could predict such negative mood was difficulties in emotion regulation. This study recommended that educational institutions should conduct periodic screening for students’ mental health and provide effective counseling services to assist students in dealing with emotional distress and adjust to university life.